2016
DOI: 10.3390/s16040432
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Terahertz Imaging at Room Temperature Employing Microbolometer Terahertz Sensors and Its Application to the Study of Carcinoma Tissues

Abstract: A terahertz (THz) imaging system based on narrow band microbolometer sensors (NBMS) and a novel diffractive lens was developed for spectroscopic microscopy applications. The frequency response characteristics of the THz antenna-coupled NBMS were determined employing Fourier transform spectroscopy. The NBMS was found to be a very sensitive frequency selective sensor which was used to develop a compact all-electronic system for multispectral THz measurements. This system was successfully applied for principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Here, µ 0 is the low-field mobility; v sat is the electron saturation velocity; F is the driving force for the charge carriers, which is the absolute value of the electric field in the simplest case and the absolute value of the gradient of a quasi-Fermi potential in our calculations; and α and β are the parameters that are adjusted to fit the experimental data. The µ(E) dependence for InGaAs was obtained by fitting the experimental data reported in [18] using formula (2), as shown in Fig. 9 (left), with the following parameters: µ 0 = 8500 cm 2 V −1 s −1 , v sat = 2.9 · 10 7 cm/s, α = 0, and β = 40.…”
Section: Influence Of High-field Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, µ 0 is the low-field mobility; v sat is the electron saturation velocity; F is the driving force for the charge carriers, which is the absolute value of the electric field in the simplest case and the absolute value of the gradient of a quasi-Fermi potential in our calculations; and α and β are the parameters that are adjusted to fit the experimental data. The µ(E) dependence for InGaAs was obtained by fitting the experimental data reported in [18] using formula (2), as shown in Fig. 9 (left), with the following parameters: µ 0 = 8500 cm 2 V −1 s −1 , v sat = 2.9 · 10 7 cm/s, α = 0, and β = 40.…”
Section: Influence Of High-field Effectsmentioning
confidence: 99%
“…operating concepts have been tested, which are used in, for example, Schottky detectors [1], microbolometer arrays [2], semiconductor field-effect transistors (FETs) with nanometric gates [3][4][5][6], and bow tie (BT)-shaped semiconductor diodes [7][8][9].…”
mentioning
confidence: 99%
“…The comparison of the metal zone plate and commercial parabolic mirror focusing performance was presented in [4]. It was shown that the imaging system with the 5 mm focal length zone plate improves the spatial resolution up to 25% in comparison with that of a commercial parabolic mirror.…”
Section: Signal (Mv)mentioning
confidence: 99%
“…It was shown that the imaging system with the 5 mm focal length zone plate improves the spatial resolution up to 25% in comparison with that of a commercial parabolic mirror. Using the same experimental set up, presented in [4], the resolution target imaging using the 50 mm diameter THz MPFL is recorded. The imaging result of the resolution target and the plastic card containing an USB stick is shown in Fig.…”
Section: Signal (Mv)mentioning
confidence: 99%
See 1 more Smart Citation